Analisis Retorika Politik Visual dan Verbal dalam Debat Keempat Calon Wakil Presiden Republik Indonesia Tahun 2024 dengan Pendekatan Aristotelian - Ilham, Muhamad Hidayatul; Jaya, Eko Pebryan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2026)
Indonesia held its General Election in 2024, during which a vice-presidential debate was conducted. The debate featured three candidates of Vice President: Muhaimin Iskandar, Gibran Rakabuming Raka, and Mahfud MD. This study examines the rhetorical abilities of these candidates by analyzing their visual and verbal political rhetoric using an Aristotelian approach, with a particular focus on the fourth debate. The research employs a descriptive qualitative method using content analysis techniques. Data were obtained from video recordings on TVRI Nasional YouTube channel. The findings shows that each candidate demonstrates distinct strengths across the dimensions of ethos, pathos, and logos. Muhaimin Iskandar and Mahfud MD exhibit strong ethos, reflected in their firm gestures and contextually grounded arguments. Gibran Rakabuming Raka, on the other hand, emphasizes pathos by building emotional connections with younger audiences and using humor to gain sympathy. All three candidates display competitive performance in terms of logos. Another important aspect is the candidates originality in terms of communication style. This study recommend that future research may adopt quantitative approaches, such as surveys or experiments, to empirically assess how audiences perceive originality, communication style, and their influence on voter preferences.